Bacterial Therapy of Cancer: Promises, Limitations, and Insights for Future Directions - Kramer, M. Gabriela; Masner, Martín; Ferreira, Fernando A.; Hoffman, Robert M. (Frontiers in Microbiology, 2018)
Spontaneous tumors regression has been associated with microbial infection for hundreds of years and inspired the use of bacteria for anticancer therapy. Dr. William B. Coley (1862-1936), a bone- sarcoma surgeon, was a pioneer in treating his patients with both live bacterial-based and mixture of heat-killed bacteria known as “Coley’s toxins”. Unfortunately, Coley was forced to stop his work which interrupted this field for about half a century. Currently, several species of bacteria are being developed against cancer. The bacterial species, their genetic background and their infectious behavior within the tumor microenvironment are thought to be relevant factors in determining their anti-tumor effectiveness in vivo. In this perspective article we will update the most promising results achieved using bacterial therapy (alone or combined with other strategies) in clinically-relevant animal models of cancer and critically discuss the impact of the bacterial variants, route of administration and mechanisms of bacteria-cancer-cell interaction. We will also discuss strategies to apply this information using modern mouse models, molecular biology, genetics and imaging for future bacterial therapy of cancer patients.